Diabetes changes gene expression but not DNA methylation in cardiac cells - Lother, Achim; Bondareva, Olga; Saadatmand, Ali R.; Pollmeier, Luisa; Härdtner, Carmen; Hilgendorf, Ingo; Weichenhan, Dieter; Eckstein, Volker; Plass, Christoph; Bode, Christoph; Backs, Johannes; Hein, Lutz; et al. (Journal of molecular and cellular cardiology, 2021)
Background - Diabetes mellitus is a worldwide epidemic that causes high mortality due to cardiovascular complications, in particular heart failure. Diabetes is associated with profound pathophysiological changes in the heart. The aim of this study was to investigate the impact of diabetes on gene expression and DNA methylation in cardiac cells. - Methods and results - Transcriptome analysis of heart tissue from mice with streptozotocin-induced diabetes revealed only 39 genes regulated, whereas cell type-specific analysis of the diabetic heart was more sensitive and more specific than heart tissue analysis and revealed a total of 3205 differentially regulated genes in five cell types. Whole genome DNA methylation analysis with basepair resolution of distinct cardiac cell types identified highly specific DNA methylation signatures of genic and regulatory regions. Interestingly, despite marked changes in gene expression, DNA methylation remained stable in streptozotocin-induced diabetes. Integrated analysis of cell type-specific gene expression enabled us to assign the particular contribution of single cell types to the pathophysiology of the diabetic heart. Finally, analysis of gene regulation revealed ligand-receptor pairs as potential mediators of heterocellular interaction in the diabetic heart, with fibroblasts and monocytes showing the highest degree of interaction. - Conclusion - In summary, cell type-specific analysis reveals differentially regulated gene programs that are associated with distinct biological processes in diabetes. Interestingly, despite these changes in gene expression, cell type-specific DNA methylation signatures of genic and regulatory regions remain stable in diabetes. Analysis of heterocellular interactions in the diabetic heart suggest that the interplay between fibroblasts and monocytes is of pivotal importance.